(untitled) - Foley, Mark ([Harlow], 2005)
To tal english elementary is correlated to the common European Framework.It covers A1 and goes towards A2.Each lesson guides students to a"Can do" goal in line with the council of Europe's "can do" statements
Keywords: English language,English language,Anh ngữ,Anh ngữ; Study and teaching,Học và dạy